Military Veterans and Their PTSD Service Dogs: Associations Between Training Methods, PTSD Severity, Dog Behavior, and the Human-Animal Bond - LaFollette, Megan R.; Rodriguez, Kerri E.; Ogata, Niwako; O'Haire, Marguerite E. (Frontiers in Veterinary Science, 2019)
Introduction. Psychiatric service dogs are increasingly being sought out by military veterans as a complementary intervention for posttraumatic stress disorder (PTSD). After receiving a service dog, many veterans continue training their service dog at home. Our objective was to explore the associations between training methods, PTSD severity, service dog behavior, and the veteran-service dog bond in a population of military veterans with PTSD. Methods. Post-9/11 military veterans with PTSD who had received a psychiatric service dog were recruited from a national service dog provider. A total of 111 veterans (M=40.1 ± 8.3 years, 80% male) participated in an online survey regarding frequency of training methods, PTSD symptom severity, service dog behavior, and the human-animal bond. Service dogs were predominately Labrador Retriever purebreds or mixes of various breeds (66% male) and mostly obtained from shelters or rescues (58%). Training methods were divided into five categories: positive reinforcement (e.g. physical praise), negative punishment (e.g. ignoring the dog), positive punishment (e.g. verbal correction), dominance (e.g. alpha roll), and bond-based (e.g. co-sleeping). Data were analyzed using general linear models. Results. Veterans self-reported using all five categories of training methods at least once a month. More frequent use of positive punishment was associated with less closeness with their service dog (p=0.02), more fear (p=0.003), less eye contact (p<0.0001), and less trainability (p=0.04). More frequent use of positive reinforcement was associated with higher closeness to their service dog (p=0.002) and perceived increased attachment behavior (p=0.002) and playfulness (p=0.002). More frequent use of bond-based methods was associated with higher closeness to their service dog (p=0.02). PTSD severity was not significantly associated with reported dog behavior, temperament, or veteran-service dog closeness. Conclusion. Military veterans with PTSD service dogs reported using many training methods that were associated with different outcomes. In general, the reported use of positive reinforcement or bond-based training methods were associated with reporting more positive outcomes while the reported use of positive punishment was associated with reporting more negative outcomes. Educating service dog organizations and recipients about the impacts of training methods could be beneficial for service dog efficacy and welfare.